A Retrospective Study: Do Hospital Menus Carry a Risk of Malnutrition? - Mendes, Beyza; Gunes Bayir, Ayse; Aksoy, Ayse Semra; Toluk, Ozlem (Wiley, 2025)
ABSTRACTMalnutrition is preventable, and increasing investment in food and nutrient care for patients can save lives. A retrospective study evaluated the adequacy levels of the menus served in a hospital by making meal‐based seasonal comparisons and examined the potential of these menus to pose a risk of malnutrition. In this context, the nutritional profile regarding energy, macro and micronutrients, and fiber was revealed. The results were compared with the Food and Drug Administration (FDA), the European Food Safety Authority (EFSA) and Türkiye Dietary Guideline‐2022 (TDG‐2022) recommendations. The nutrient profile of the menus was assessed by the Nutrient Rich Food NRF20.3 index (NRF20.3) and Limiting Nutrients 3 (LIM3) subscores. A one‐year dataset obtained from a hospital menu includes three meals (breakfast, lunch, and dinner) with various menus (general, diabetic, and gluten‐free) were examined, and the results of their nutrient profile were significantly different (p = 0.001). The NRF20.3 score for all menus and meals for a year was insignificant, while LIM3, the general menus for breakfast in spring, were higher than those of other menus (p = 0.001). The energy content of the general menus was between 1,621 and 1,663 kcal, which is high according to TDG‐2022, instead of EFSA and FDA. Daily potassium, calcium, magnesium, and fiber of the menus were low according to TDG‐2022 and EFSA, which is in accordance with including more meat and fewer vegetables, fruits, and dairy groups seasonally. Sodium and phosphorus in the menus were high. It was seen that the nutrient profile of the hospital menus examined in the study was not compatible with TDG‐2022. The menus' high energy, fat, saturated fat, sodium, and low calcium and fiber content lead to imbalances in nutrient intake. This situation can lead to nutrient deficiencies in hospitalized individuals. However, when the amount of protein in the menus is considered, it is seen that hospital menus pose a risk of malnutrition for men while being sufficient for women.
Keywords: Original Article